The constitutional procedural law in expansion (chronicle of a growth) - García Belaunde, Domingo (2007)
The author makes a historic account of the Constitutional Procedural Law, settling the birth of this discipline in the forties in Argentina, product of the work by the Spanish procedural expert Niceto Alcalá Zamora (exiled in this country), and its development in Mexico, product of the special dedication of Héctor Fix-Zamudio. From the moment of its birth, the author realizes a severe investigation about the development of the Constitutional Procedural Law in Mexico, South America, Central America and the Caribbean, stopping at each country to present its bibliographic production and the studies there made on the subject. He also presents the European panorama, making a special reference to France, Spain, Italy and Germany. Finally, the author concludes that the Constitutional Procedural Law confronts serious problems, from its very name to the subjects it must treat, those which are part of its aim, without disregarding its location or nature.